Effects of Qiang Gu Kang Wei prescription on morphology of bone in rats under simulated weightlessness - Li, Yong-zhi; Shi, Hong-zhi; Fan, Quan-chun; Tao, Ying; Bai, Gui-e; Duan, Yuan-ru; Xie, Jun-shui (Hang tian yi xue yu yi xue gong cheng, 2003)
To investigate effects of Qiang Gu Kang Wei prescription on bone morphology in tail-suspended rats. Rats were tail-suspended (-30 degrees) for 21 d to simulate weightlessness. The effects of this prescription on thickness of periost and cortex at epiphyseal plate of tibial shaft and 3 mm under it were examined. The effects of this prescription on histology and ultrastructure of tibia were also observed. Compared with the normal control, cortex at both epiphyseal plate of tibial shaft and 3 mm under it in suspended rats thinned significantly (P<0.01 or P<0.05). Histological observation showed that in bone of suspended rats, uncalcific matrix was more, bone cells' number was lower and their appearance was more infantile, osteoblasts were less and smaller, while osteoclasts were more and larger, haversian system of transection also showed more irregular than in bone of normal control. Ultrastructure observation showed that the function of osteoblasts was inhabited and that of osteoclasts was active. All the thre